UNİQUE CHARACTERISTICS OF FOREX MARKETS AND COMPARASION OF FOREX MARKET WITH STOCK MARKETS AND FUTURES MARKETS - Yeşim ŞENDUR (Fırat University, 2019)
Abstract Attention to Forex Market is increasing day after day throughout the world. Until the beginning of the 1990’s the access to the Forex Markets is traditionally restricted to big companies, hedge funds and the other corporate investors. The biggest banks of the world have been operating at this market for many years. Self-directed (retail) investors couldn’t enter into the market for a long time since they don’t have any chance to compete with the big players of the market. After 1990’s the Forex Market has started to open its gate to the retail investors. The market makers of the Forex Market transform the big buy and sell positions to small ones which are proper to retail investors. These lead to retail investors to trade among the big players of the forex markets via using the professional’s strategies and techniques. Thus retail investors gain a new investment area besides stock markets and futures markets. Forex Market, which resembles the other markets in some aspects, has its own characteristics. These characteristics distinguish its structure from other markets. Being a global 24-hour open market, having the highest daily volume thereby the highest liquidity among the other financial markets, possibility of buy and sell order at anytime, possibility of utilizing highest leverage in comparison with other markets and lower transaction costs are the features which differ Forex Markets from other financial markets. In recent years the intermediary institutions try to raise awareness of investors by emphasizing the differences between the markets. If an investor knows the unique characteristics of the Forex Market, it helps the investor to make a good decision about which market he or she is going to invest.